Karakteristik Edible Film dengan Penambahan Filtrat Gambir (Uncaria gambir Roxb) dan Filtrat Daun Pepaya (Carica papaya L.) - Budi Santoso; Herawati Herawati; Gatot Priyanto (Seminar Nasional Lahan Suboptimal, 2018)
Santoso et al, 2019. Characteristics of Edible Film with Addition of the Gambir Filtrate (Uncaria gambir Roxb) and Papaya Leaf Filtrate (Carica papaya L.). pp. 176-183.Edible film is a thin layer of biodegradable packaging made from hydrocolloid, lipid and a mixture of both and can serve as a carrier packaging for antibacterial compounds with adding gambir filtrate and papaya leaf filtrate. The objective of the research was to analyze the effect of the gambir filtrate (Uncaria gambier Roxb) and papaya leaf filtrate (Carica papaya L.) on the characteristics of edible film. The research used a Completely Randomized Factorial Design with two factors and each treatment was repeated three times. The frist factor was concentration of the filtrate Gambir (0%, 2.5% and 5%) and the second factor was the concentration of the papaya leaf filtrate (0%, 2.5% and 5%). The research showed that the concentration of the filtrate gambir significant effect on percent of elongation, antibacterial, thickness and water vapour transmission rate. The concentration of the papaya leaf filtrate significantly affected the antibacterial, thickness, percent of elongation and a pressure strength. The best treatment based on some physical and microbiological characteristics is that A3B3 has a thickness 0.174 mm, percent of elongation 20%, pressure strength 90.80 (N / m2), water vapour transmission rate 21.16 (gm-2.day-1) and a inhibition zone for microbe 7.97 mm.